(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article provides a comprehensive analysis of the formation of the concept of a green economy, its modern development trends and its role in the global economy. The research study examines economic mechanisms aimed at ensuring sustainable development, efficient use of resources, prevention of climate change and environmental safety. It also highlights the impact of green technologies, renewable energy sources, carbon emission reduction policies in developed and developing countries, and the impact of “green” investments on global economic growth.